Long-Term Follow-Up After Treatment of Drug-Eluting Stent Restenosis and De Novo Lesions Using SeQuent Please Paclitaxel-Coated Balloons. (May 2019) - Zhang, Dai; Sun, Yan; Liu, Xiaoli; Liu, Fang; Cheng, Yujing; Ma, Xiaoteng; Zhao, Yingxin; Zhou, Yujie
Managing patients with in-stent restenosis (ISR) remains an important clinical challenge. In particular, large, randomized trials assessing the effect of drug-eluting balloons (DEB) in patients with de novo lesions are warranted. We investigated the effect of DEB on procedural complications, target lesion revascularization (TLR), and major adverse cardiac and cerebrovascular events in patients with drug-eluting stent ISR and de novo lesions. The clinical profiles of 238 consecutive patients treated for coronary ISR (n = 174) and de novo lesions (n = 64) using SeQuent Please paclitaxel-coated balloon were analyzed. Study end points were major adverse cardiac events (MACEs). At 1-year follow-up, TLR and MACEs occurred with acceptably low rates (5.0% and 6.3%, respectively). At 2.00 (0.74) years of follow-up, there was a significant difference in the rates of TLR between the ISR and the de novo lesions groups (14.4% [ISR] vs 3.1% [de novo], P = .028), and the occurrence of MACEs distinctly increased in the ISR group compared to the de novo lesions group (21.8% vs 6.2%, P = .009). The long-term outcomes of the ISR group were inferior to those of the de novo group (TLR, log-rank P = .019; MACEs, log-rank P = .010). Drug-eluting balloon for ISR and de novo lesions of small coronary vessels is effective and safe.